1984
DOI: 10.1002/j.1537-2197.1984.tb14141.x
|View full text |Cite
|
Sign up to set email alerts
|

Somaclonal and Gametoclonal Variation

Abstract: For several years it has been recognized that introduction of plant cells into culture results in genetic changes. These genetic alterations have been recovered in the plants regenerated from cell cultures. More recently it has been recognized that this method of introducing genetic changes into crop plants could be used to develop new breeding lines. The technology of introducing genetic variation by using cell culture has been termed somaclonal and gametoclonal variation. This paper reviews the history of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
9

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(66 citation statements)
references
References 48 publications
3
53
1
9
Order By: Relevance
“…Isozyme patterns have been used to detect changes during regeneration as they play a vital role in development and differentiation (Orton 1983, Evans et al 1984, Chawla 1988. Isozyme study has been suggested as a valuable tool in identifying genetic and epigenetic changes (Michel 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Isozyme patterns have been used to detect changes during regeneration as they play a vital role in development and differentiation (Orton 1983, Evans et al 1984, Chawla 1988. Isozyme study has been suggested as a valuable tool in identifying genetic and epigenetic changes (Michel 1975).…”
Section: Discussionmentioning
confidence: 99%
“…As três plantas que apresentaram resistência moderada, e utilizadas para nova indução de calos e regeneração das plantas, mostraram maior variabilidade no tocante a todas características, incluindo resistência à brusone. O incremento nas variações desejadas foi obtido através do segundo ciclo de seleção, conforme o procedimento sugerido por Evans et al (1984). Estes resultados mostraram a importância da indução e da regeneração, a partir de plantas nas gerações iniciais de cultivo de células.…”
Section: Resultsunclassified
“…Mutações gênicas foram comumente obtidas em somaclones, e uma das estratégias de melhoramento inclui a utilização da cultivar melhorada para incorporação de uma característica específica como resistência às doenças, mediante a cultura de tecidos. O incremento de variabilidade genética para características desejáveis pode ser obtido a partir de plantas R 2 que não apresentaram grau de resistência adequado (Evans et al, 1984).…”
Section: Introductionunclassified
“…However, the somaclonal variations have a great potential for the crop-improvement [7]. These variations have been evaluated for morphological traits like pigment production, biochemical characters like nicotine synthesis, chromosome number and structure [8]. Somaclonal variations can be artificially induced by in vitro mutagenesis using various physical as well as chemical agents and by the polyploidation.…”
Section: Introductionmentioning
confidence: 99%